High-energy sources at low radio frequency: The Murchison Widefield Array view of Fermi blazars - Giroletti, M.; Massaro, F.; D'Abrusco, R.; Lico, R.; Burlon, D.; Hurley-Walker, Natasha; Johnston-Hollitt, M.; Morgan, J.; Pavlidou, V.; Bell, M.; Bernardi, G.; Bhat, Ramesh; et al. (EDP Sciences, 2016)
© ESO 2016. Context. Low-frequency radio arrays are opening a new window for the study of the sky, both to study new phenomena and to better characterize known source classes. Being flat-spectrum sources, blazars are so far poorly studied at low radio frequencies. Aims. We characterize the spectral properties of the blazar population at low radio frequency, compare the radio and high-energy properties of the gamma-ray blazar population, and search for radio counterparts of unidentified gamma-ray sources. Methods. We cross-correlated the 6100 deg2 Murchison Widefield Array Commissioning Survey catalogue with the Roma blazar catalogue, the third catalogue of active galactic nuclei detected by Fermi-LAT, and the unidentified members of the entire third catalogue of gamma-ray sources detected by Fermi-LAT. When available, we also added high-frequency radio data from the Australia Telescope 20 GHz catalogue. Results. We find low-frequency counterparts for 186 out of 517 (36%) blazars, 79 out of 174 (45%) gamma-ray blazars, and 8 out of 73 (11%) gamma-ray blazar candidates. The mean low-frequency (120-180 MHz) blazar spectral index is (alow) = 0.57 ± 0.02: blazar spectra are flatter than the rest of the population of low-frequency sources, but are steeper than at ~GHz frequencies. Low-frequency radio flux density and gamma-ray energy flux display a mildly significant and broadly scattered correlation. Ten unidentified gamma-ray sources have a (probably fortuitous) positional match with low radio frequency sources. Conclusions. Low-frequency radio astronomy provides important information about sources with a flat radio spectrum and high energy. However, the relatively low sensitivity of the present surveys still misses a significant fraction of these objects. Upcoming deeper surveys, such as the GaLactic and Extragalactic All-Sky MWA (GLEAM) survey, will provide further insight into this population.